Antioxidant Peptides From Protein Hydrolysate of Marine Red Algae Eucheuma cottonii: Preparation, Identification, and Cytoprotective Mechanisms on H2O2 Oxidative Damaged HUVECs - Sun, Kun-Lai; Gao, Min; Wang, Yue-Zhen; Li, Xue-Rong; Wang, Peng; Wang, Bin (Frontiers in Microbiology, 2022)
To screen, prepare, identify, and evaluate the activities of natural antioxidants for treating chronic diseases caused by oxidative stress. Two algal proteins, namely ZD10 and ZD60, precipitated with 10 and 60% (NH4)2SO4 were extracted from red algae Eucheuma cottonii (E. cottonii) and hydrolyzed using five proteolytic enzymes. The results showed that ZD60 played the most significant role in the enhancement of 2,2-diphenyl-1-picrylhydrazyl radical (DPPH⋅) scavenging activity (25.91 ± 0.24%) among all protein hydrolysates. Subsequently, six antioxidant peptides (EP1-EP6) were isolated from the papain hydrolysate of ZD60 by ultrafiltration and chromatography methods. Their amino acid sequences were identified as Thr-Ala (EP1), Met-Asn (EP2), Tyr-Ser-Lys-Thr (EP3), Tyr-Ala-Val-Thr (EP4), Tyr-Leu-Leu (EP5), and Phe-Tyr-Lys-Ala (EP6) with molecular weights of 190.21, 263.33, 497.55, 452.51, 407.51, and 527.62 Da, respectively. Of which, EP3, EP4, EP5, and EP6 showed strong scavenging activities on DPPH⋅, hydroxyl radical (HO⋅), and superoxide anion radical (O- 2⋅). Moreover, EP4 and EP5 could significantly protect human umbilical vein endothelial cells (HUVECs) from H2O2-induced oxidative damage by increasing the levels of antioxidant enzyme systems including superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) to reduce the levels of reactive oxygen species (ROS) (60.51 and 51.74% of model group) and malondialdehyde (MDA) (75.36 and 64.45% of model group). In addition, EP4 and EP5 could effectively inhibit H2O2-induced apoptosis by preventing HUVECs from early apoptosis to late apoptosis. These results indicated that the antioxidant peptides derived from E. cottonii, especially EP4 and EP5, could serve as the natural antioxidants applied in pharmaceutical products to treat chronic cardiovascular diseases caused by oxidative damage, such as coronary heart disease, atherosclerosis, etc.